Coping Strategies in Overcoming Stress in Farmers After Crop Failure - Fadhilla, Ailsa Ayu; Salsabila, Yolanda Nandin; Susanti, Nadia Indri; Kurniyawan, Enggal Hadi; Nur, Kholid Rosyidi Muhammad; Afandi, Alfid Tri; Kurniawan, Dicky Endrian (Rajaki of Tulip Medika Publisher, 2025)
Crop failure often happens to farmers, so they are vulnerable to considerable losses, and farmers experience psychosocial disorders such as stress, sadness, and anxiety due to crop failure. When facing crop failure, it is necessary to have a stress-coping strategy to help farmers control their emotions. The method used was a literature review, with a search using three databases, namely Google Scholar, Pubmed, and ScienceDirect, using the keywords psychosocial, farmers, crop failure, and coping mechanisms. The journal articles used for review were 10 journals, with four international and six national journals. Psychosocial pressure on farmers is marked by increased stress in the form of anxiety, disappointment, low self-esteem, antisocial behavior, and loss of motivation to return to farming. Stress coping mechanisms carried out by farmers are perfect for controlling farmers facing crop failure. Besides, farmers have different coping mechanisms; for example, some do their favorite hobbies to distract their minds; on the other hand, some choose relaxation therapy and pray to calm their minds. Stress coping management is effective in helping farmers manage emotions when experiencing crop failure; many farmers can control stress when experiencing crop failure even though they divert it to something positive and some to something negative. In addition to crop failure, stress-coping management strategies can also overcome problems related to farmers' work.